Bone Scans Are Reliable for the Identification of Lumbar Disk and Facet Pathology. (February 2015) - Malham, Gregory M.; Parker, Rhiannon M.; Ballok, Zita E.; Goss, Ben; Diwan, Ashish D.; Uribe, Juan S.
Study Design: Surgeon survey. Objective: To evaluate the reliability of bone single-photon emission computed tomography (SPECT) versus bone SPECT images co-registered with computed tomography (bone SPECT-CT) by analyzing interobserver agreement for identification of the anatomical location of technetium 99m -labeled oxidronate uptake in the lumbar disk and/or facet joint. Methods: Seven spine surgeons interpreted 20 bone scans: 10 conventional black-and-white tomograms (bone SPECT) and 10 color-graded bone SPECT-CT scans. Each surgeon was asked to identify the location of any diagnostically relevant uptake in the disk and/or facet joint between L1 and S1. Reliability was evaluated using the free-marginal kappa statistic, and the level of agreement was assessed using the Landis and Koch interpretation. Results: Conventional bone SPECT scans and bone SPECT-CT scans were reliable for the identification of diagnostically relevant uptake, with bone SPECT-CT having higher reliability (kappa = 0.72) than bone SPECT alone (0.59). Bone SPECT and bone SPECT-CT were also reliable in identifying disk pathology, with kappa values of 0.72 and 0.81, respectively. However, bone SPECT-CT was more reliable (0.81) than bone SPECT (0.60) when identifying facet disease. Conclusions: For the identification of disk pathology, it is reasonable to use either conventional bone SPECT or bone SPECT-CT; however, bone SPECT-CT is more reliable for facet joint pathology.